Replacement of Nitrite in Meat Products by Natural Bioactive Compounds Results in Reduced Exposure to N‐Nitroso Compounds: The PHYTOME Project - Breda, Simone G.; Mathijs, Karen; Pieters, Harm‐Jan; Sági‐Kiss, Virág; Kuhnle, Gunter G.; Georgiadis, Panagiotis; Saccani, Giovanna; Parolari, Giovanni; Virgili, Roberta; Sinha, Rashmi; Hemke, Gert; Hung, Yung; et al. (Molecular nutrition & food research, 2021)
Scope It has been proposed that endogenously form N‐nitroso compounds (NOCs) are partly responsible for the link between red meat consumption and colorectal cancer (CRC) risk. As nitrite has been indicated as critical factor in the formation of NOCs, the impact of replacing the additive sodium nitrite (E250) by botanical extracts in the PHYTOME project is evaluated. Method and Results A human dietary intervention study is conducted in which healthy subjects consume 300 g of meat for 2 weeks, in subsequent order: conventional processed red meat, white meat, and processed red meat with standard or reduced levels of nitrite and added phytochemicals. Consumption of red meat products enriched with phytochemicals leads to a significant reduction in the faecal excretion of NOCs, as compared to traditionally processed red meat products. Gene expression changes identify cell proliferation as main affects molecular mechanism. High nitrate levels in drinking water in combination with processed red meat intake further stimulates NOC formation, an effect that could be mitigated by replacement of E250 by natural plant extracts. Conclusion These findings suggest that addition of natural extracts to conventionally processed red meat products may help to reduce CRC risk, which is mechanistically support by gene expression analyses. The PHYTOME project develops innovative meat products in which the food additive nitrite was replaced by natural compounds originating from fruits and vegetables. These biologically active compounds (phytochemicals) contribute to improved gut health. Subjects consuming red processed meat enriched with phytochemicals formed lower levels of potentially carcinogenic N‐nitroso compounds in their gut, which may reduce their risk on colorectal cancer.